Hiter in preprost algoritem za razdvoumljanje simbolov genov - Kastrin, Andrej (Informatica Medica Slovenica, 2008)
Gene symbol disambiguation is an important problem for biomedical text mining systems. When detecting gene symbols in MEDLINEr citations one of the biggest challenges is the fact that many gene symbols also denote other, more general biomedical concepts (e.g. CT, MR). Our approach to this problem is first to classify the citations into genetic and nongenetic domains and then to detect gene symbols only in the genetic domain. We used ontological information provided by Medical Subject Headings (MeSHr) for this classification task. Theproposed algorithm is fast and is able to process the full MEDLINE distribution in a few hours. It achieves predictive accuracy of 0,91. The algorithm is currently implemented in the BITOLA literature-based discovery support system.
Keywords: Algorithms; Algoritmi; Deskriptorji; Genes; genetika; Geni; Medline; Nomenclature; Subject Headings